Prevalence of Dermatological Presentations of Canine Leishmaniasis in a Nonendemic Area: A Retrospective Study of 100 Dogs. (5th February 2014) - Perego, Roberta; Proverbio, Daniela; Bagnagatti De Giorgi, Giada; Spada, Eva
Abstract : This retrospective study determined the prevalence of dermatological lesions associated with canine leishmaniasis (CanL) in a nonendemic area in Italy. The medical records of 131 dogs with CanL were reviewed and, of these, 115/131 dogs (88%) had dermatological manifestations of which 100/131 dogs (76%) met the inclusion criteria. Sixty-two percent of dogs were male and 38% were female and the mean age was 6.4 years. Thirty-two percent of dogs were mixed breeds; the remainder represented a variety of pure breeds. In 79% of dogs dermatological signs occurred in association with systemic signs of CanL, whilst 21% of dogs had only dermatological manifestations. The most common dermatological manifestation was exfoliative dermatitis (74%), followed by ulcerative (18%) and nodular (11%) lesions. In 51% of dogs the lesions were localized mainly on the pinnae, head, and pressure points; in the remaining 49% lesions were generalized. The only statistically significant association was between Retriever breed and animals with only dermatological signs (P = 0.0034, OD 5.97, CI 0.996–37.933). In this study dermatological manifestations of CanL were very commonly reported, and their prevalence is similar to previous studies in endemic areas despite the fact that dogs living in nonendemic areas are not exposed to repeated infectious bites and continuous stimulation of the dermal immune system.